2002
DOI: 10.1021/jm020235g
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde-Induced DNA Cross-Link of Indolizino[1,2-b]quinolines Derived from the A−D Rings of Camptothecin

Abstract: Camptothecin consists of a lactone E ring adjacent to tetracyclic A-D rings of a planar chromophore, which are essential for topoisomerase I inhibition and DNA interaction. The A-D rings can be exploited to develop DNA-sequence-reading molecules. Indolizino[1,2-b]quinoline derivatives substituted with a piperidinoethyloxy side chain and an aminomethyl function on rings A and D, respectively, were synthesized, and their DNA binding and formaldehyde-mediated bonding properties were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In Scheme , few synthetic applications of the known methodology are depicted. In particular, the Bechamp reduction is suitable for the reduction of nitroarenes a to give anilines b as starting building block for the synthesis of 9,11-dihydroindolizino­[1,2- b ]­quinolines c , which are biologically active compounds (Scheme a) . Indium was also used in the “all water” synthesis of substituted benzimidazoles d (Scheme b) .…”
Section: Metal Dissolving Reductionsmentioning
confidence: 99%
“…In Scheme , few synthetic applications of the known methodology are depicted. In particular, the Bechamp reduction is suitable for the reduction of nitroarenes a to give anilines b as starting building block for the synthesis of 9,11-dihydroindolizino­[1,2- b ]­quinolines c , which are biologically active compounds (Scheme a) . Indium was also used in the “all water” synthesis of substituted benzimidazoles d (Scheme b) .…”
Section: Metal Dissolving Reductionsmentioning
confidence: 99%
“…Quinoline | 639 ROMERO Et al. alkaloids derived from plants, animals, and micro-organisms have showed remarkable antitumor activity against different cancer cells (Jain, Chandra, Jain, Pathak, & Vaidya, 2016). Also, several examples of synthetic quinolines have been reported by multiple research groups worldwide as promising anticancer agents (Beauchard et al, 2009;Czoch, Pognan, Kaczmarek, & Boraty, 1994;Ferlin, Gatto, Chiarelotto, & Palumbo, 2001;Gamal, Khan, Maksoud, El-Din, & Oh, 2014;Heiniger, Gakhar, Prasain, Hua, & Nguyen, 2010;Kim et al, 2001;Martirosyan, Rahim-Bata, Freeman, Clarke, & Howard, 2004;Perzyna et al, 2002;Tseng, Chen, Lu, Yang, & Tzeng, 2008;Tseng et al, 2009Tseng et al, , 2010Utsugi et al, 1997). In particular, compounds based on 4-aminoquinolines have received largely attention by its significant anticancer activity (Chen, Chen, Wang, Han, & Tzeng, 2005;Chen, Chung, Chen, Chen, & Jeng, 2002;Chen et al, 2006Chen et al, , 2011Kakadiya et al, 2010;Lee et al, 2004;Lu et al, 2010;Mejía et al, 2009;Sanchez et al, 2011;Su et al, 1995;Via, Gia, Gasparotto, & Ferlin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, antimalarial drugs such as chloroquine, hidroxychloroquine, mefloquine, quinine, and quinacrine have demonstrated an appreciable antiproliferative effect against different cancer cells, exhibiting sub-micromolar IC 50 values (Choi, Kim, Woo, Kim, & Yoon, 2016;Grimaldi et al, 2015;Maes, Kuchnio, Carmeliet, & Agostinis, 2016;Preet et al, 2012;Salentin et al, 2017;Verbaanderd et al, 2017;Yan et al, 2013). In general, most of the anticancer quinolines are targeted to tyrosine kinase enzymes, proteasome, tubuline polymerization, topoisomerase, or DNA repair (Beauchard et al, 2009;Czoch et al, 1994;Ferlin et al, 2001;Gamal et al, 2014;Heiniger et al, 2010;Kim et al, 2001;Martirosyan et al, 2004;Perzyna et al, 2002;Tseng et al, 2008Tseng et al, , 2009Tseng et al, , 2010Utsugi et al, 1997). Modulation of the large-conductance calcium-activated potassium (BK) channels also has been identified as target for 4-substituted quinolines and 4-substituted quinolin-2-ones, representing an attractive target for the 4-aminoquinolines tested in this investigation (Dinsmore & Bergman, 2003;Hewawasam, Sit, & Starrett, 2003;Hewawasam, Starrett, & Swartz, 1997;Kang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigation and modification of CPT brought fruits with two antitumor agents approved by the FDA: topotecan for small-cell lung cancer and irinotecan for refractory colorectum cancer . Further study showed that the ABCD rings of CPT function as the pharmacophore responsible for binding to DNA . Thus, developing practical and efficient strategies for acquiring different substituted indolizino­[1,2- b ]­quinolin-9­(11 H )-ones has great significance to improve the clinical application of the camptothecin family.…”
Section: Introductionmentioning
confidence: 99%